Not all that swells is angioedema: a hidden malignancy - Yildirim, Harun; Demir, Betul; Calik, Ilknur; Balci, Mustafa; Yildirim, Ebru Aydin; Yildirim, Hanefi (Wiley, 2026)
[Abstract Not Available]
Keywords: Angioedema; small cell lung cancer; superior vena cava syndrome